Material and solar cell research in microcrystalline silicon - Shah, Arvind; Meier, Johannes; Vallat-Sauvain, Evelyne; Wyrsch, Nicolas; Kroll, U.; Droz, C.; Graf, U. (My University, 2003)
This contribution describes the introduction of hydrogenated microcrystalline silicon (μc-Si:H) as novel absorber material for thin-film silicon solar cells. Work done at IMT Neuchâtel in connection with deposition of μc-Si:H layers by very high frequency glow discharge deposition is related in detail. Corresponding layer properties w.r.t. material microstructure, hydrogen content, stability and electronic transport are referred to. Basic properties of single-junction, entirely microcrystalline, thin-film silicon solar cells are related: Spectral response, stability w.r.t. light-induced degradation, basic solar cell parameters (Voc, Jsc and FF) obtained by IMT Neuchâtel and by other laboratories are listed and commented; the deposition rate issue is addressed. Finally, microcrystalline/amorphous, i.e. “micromorph” silicon tandem solar cells, are described, together with recent developments on the research and industrial front.
Keywords: microcrystalline silicon; plasma deposition; material properties; electronic transport; single-junction solar cells; tandem solar cells